(untitled) (Global Journal of Human-Social Science, 2023)
Information about the location and ethnic history of the Turkmen population in the Zarafshan region can be found in scientific works published by several experts However fel scientific articles fully reflect this historical process This article covers the history of Turkmen ethnic groups living in Uzbekistan the settlement history and the geographical location of the Zarafshan basin